Experimental and analytical optical-thermal performance of evacuated cylindrical tube receiver for solar dish collector. (1st November 2021) - Yuan, Yu; Wu, Gang; Yang, Qichang; Cheng, Ruifeng; Tong, Yuxin; Zhang, Yi; Fang, Hui; Ma, Qianlei
Abstract: Evacuated cylindrical tube receiver (ECT) is a promising type of solar collector system, due to its mass production, low cost, and low heat loss. In this paper, a solar dish collector system with evacuated cylindrical tube receivers (SDEC) is proposed, designed and trial-manufactured. The optical-thermal efficiency and economic analysis are carried out to validate the comprehensive performance of the SDEC. The results show that the thermal efficiency of the SDEC is about 47.3%. The nonuniformity of the solar flux and temperature distributions at the top of the absorber are verified through the coupled multiphysics simulation with the result of 0–50 mm. In addition, over 10 years of the lifetime of the SDEC with 20 ECTs, the cumulative present worth of annual saving for heat production turned out to be approximately 34, 041 and 13, 460 with respect to electricity coiler and gas-fired boiler, respectively, when the cost of heat production per kWh is 0.0264 and the payback period is 1.88 years. Highlights: Combine an evacuated cylindrical tube receiver with a parabolic dish concentrator. Optical-thermal efficiency and economic analysis were carried out. The thermal efficiency of the SDEC is about 47.3%. The cost of heat production per kWh worked out to be 0.0264.